2010
DOI: 10.1177/1065912910382301
|View full text |Cite
|
Sign up to set email alerts
|

What is Relevance? Defining Intersectional Praxis in Uruguay

Abstract: This article examines intersectional praxis via a focus on what constitutes relevant axes of difference. The author argues that a discussion of relevance should focus on two important issues: (1) which categories are of analytic importance and (2) those categories that activists consider relevant. This approach allows for activist debates over the most important social divisions in society while establishing some minimal number of axes that must be included to qualify activism as intersectional. In the Uruguay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 22 publications
1
23
0
1
Order By: Relevance
“…Others, however, have pointed to problems in implementing this approach; for example, Ward () reported that although social activists struggled ‘not to count, emphasize, and prioritize particular oppressions’ (p. 99), it was still difficult to build coalitions for change across groups. A similar finding was reported by Townsend‐Bell () on the applicability of intersectionality in collaborative social movement building in Uruguay, where disagreements over the relevance of specific identity categories hindered the development of a multi‐issue approach to equality in a national women's rights coalition.…”
Section: Introductionsupporting
confidence: 79%
“…Others, however, have pointed to problems in implementing this approach; for example, Ward () reported that although social activists struggled ‘not to count, emphasize, and prioritize particular oppressions’ (p. 99), it was still difficult to build coalitions for change across groups. A similar finding was reported by Townsend‐Bell () on the applicability of intersectionality in collaborative social movement building in Uruguay, where disagreements over the relevance of specific identity categories hindered the development of a multi‐issue approach to equality in a national women's rights coalition.…”
Section: Introductionsupporting
confidence: 79%
“…We use the construct of ‘markers of inequality’ (Antonucci et al , ) to refer to the specific indicators — physical, symbolic, discursive and structural — that get attached to particular differences to co‐construct inequalities that result in differential outcomes in advancement opportunities. An emic approach that identified emergent categories of difference ‘as embedded in a specific time and place’ (Tatli and Özbilgin, , p. 180) was adopted in order to understand social categories and the intersectionality of differences within a particular socio‐economic and cultural context and to stay away from pre‐determined classificatory schemas of ‘culture’ (Calás, ; Townsend‐Bell, ). We sought to identify what ‘markers’ or ‘indicators’ of gender, class and racio‐ethnicity employees and managers constructed as important, through discourse, interactions and reported experience.…”
Section: Methodsmentioning
confidence: 99%
“…Second, in contrast with case studies that focus on one national context and/or one type of organization (e.g., Roth 2004;Strolovitch 2007;Townsend-Bell 2011), the comparative framework I propose makes it possible to analyze when and why organizations use one repertoire rather than another, and allows us to reflect on the conditions that favor or impede the use of intersectionality. So far, two factors have been identified in the literature as conducive to greater inclusion of minority women's interests in coalitions or political platforms.…”
Section: Intersectionality and Women's Movementsmentioning
confidence: 99%